Building Critical Thinking and Tolerance through Qualitative Methodology Subject - Raihani, Raihani (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2025)
Using the methods of autoethnography and phenomenology, this study describes the teaching of the qualitative research methodology at the Islamic Educational Management (IEM) department within UIN Sultan Syarif Kasim Riau and its impacts on students’ academic skills. As literature suggest, research methodology courses can be useful in developing academic skills of students including analytical and critical thinking. Qualitative research courses particularly contribute to students’ more open and tolerant attitudes towards differences of social reality. This study confidently reveals such benefits of the course and further found that students experienced through a journey of emotional struggles such as anxiety, stress, and worries and of intellectual shifts to become more independent, open-minded, critical, and tolerant individuals. This study implies that a more serious commitment both from the system and the lecturer to the teaching of this course would enhance high outcomes to help university students to be better persons fitting the increasingly demanding society.